Profiling of Peripheral TRBV and CD4+CD25+ Treg in CHB Patients with HBeAg SC during TDF Treatment. (10th January 2023) - Yang, Jiezuan; Lu, Haifeng; Chen, Baikun; Jiang, Lili; Zhang, Hua; Ye, Ping; Jin, Linfeng
Abstract : Background . It is lacking that markers could predict the prognosis of chronic hepatitis B (CHB) subjects during antiviral treatment, and the related cellular immune mechanism is not fully evaluated. Aim . To explore the comprehensive profile of T cell receptor β -chain (TRBV) and CD4+CD25+ regulatory T cell (Treg) in peripheral blood of CHB patients with HBeAg seroconverting (SC) during tenofovir disoproxil fumarate (TDF) treatment. Methods . The frequency of CD4+CD25high+ Treg and number of skewed TRBV in 20 HBeAg positive patients were determined at baseline and following every 12 weeks during 96-week TDF treatment. The relationship among serum alanine aminotransferase (ALT) level, HBV DNA load, Treg frequency, and the number of skewed TRBV, respectively, was analyzed for CHB patients. Receiver operative characteristic curve was applied to analyze their diagnostic value for HBeAg SC. Results . The number of skewed TRBV at week 48, Treg frequency at week 72, and ALT level at baseline could predict the HBeAg SC or non-SC in CHB patients during 96-week TDF treatment. Moreover, the positive correlation between ALT or HBV DNA and Treg levels or skewed TRBVs was significant in the SC group, but not in non-SC. Conclusions . The predictive cutoff value of ALT for HBeAg SC was 178 U/L at baseline. Moreover, the ALT, Treg, and TRBV families would be associated with the prognosis and pathogenesis of CHB patients during TDF treatment.